Improved in-situ direct shear test of rock mass structural plane and its application to stability analysis of bedding slope - Zhiming Wang; Changguang Qi; Zhichao Zhang; Rufa Huang; Chaoxu Guo; Lijin Dong; Rongyue Zheng (Case Studies in Construction Materials, 2025)
Landslides along bedding planes are a common type of rocky landslide, and the shear strength parameters of structural planes play a crucial role in the stability of bedding slopes. Previous tests of shear strength parameters for rock mass structural planes have mostly focused on laboratory experiments, which inevitably suffer from sample disturbance, boundary effects, size effects, and grading scale error. An improved in-situ direct shear test method, utilizing an angle-adjustable leveling steel frame adapted to the rock mass structural planes with different dip angles was developed to test the shear strength parameters of the rock mass and its structural planes in natural and saturated states on a bedding rocky slope. The test results show that the shear strength parameters of the rock mass are: cohesion c=50.4kPa and friction angle φ=411° in natural state; The cohesion c=34.6kPa and friction angle φ=41.8° in saturated state. The shear strength parameters of the structural planes are: cohesion c=49.0kPa and friction angle φ=27.1° in natural state; The cohesion c=24.8kPa and the friction angle φ=28.0° in saturated state. The shear stress-shear displacement curves of the rock mass and its structural planes in the natural state show strain softening characteristics with some brittle damage, while the shear stress-shear displacement curves in the saturated state show a slight strain hardening characteristic. The numerical simulation shows that the unsupported slope is in a critical state, and the dangerous structural plane is determined. Based on this, a reasonable supporting scheme is proposed. The conclusion of this study verifies the feasibility and validity of the improved in-situ direct shear test method in the testing of the shear strength parameters of rock structural plane. It solves the problem that the previous in-situ direct shear test is too complicated and has poor applicability, and it can obtain the shear strength parameters of rock structural plane more accurately and conveniently. Hence, it provides a more reasonable parameter selection basis for the evaluation and support design of bedding rocky slope.